The symptom of low mood in the prodromal stage of mild cognitive impairment and dementia: a cohort study of a community dwelling elderly population. Issue 7 (6th January 2011) - Caracciolo, B; Bäckman, L; Monastero, R; Winblad, B; Fratiglioni, L
Abstract : Objective: To investigate the symptom of low mood as a predictor of mild cognitive impairment (MCI) and its progression to dementia, taking into account: (i) MCI severity, (ii) time of assessment and (iii) interaction with other factors. Methods: 764 cognitively healthy elderly subjects living in the community, from the Kungsholmen Project. Participants were assessed by direct interview to detect low mood. Subjects were then followed for 6 years to identify those who developed MCI. People with incident MCI were followed for a further 3 years to assess progression to dementia. Results: People with low mood at baseline had a 2.7-fold (95% CI 1.9 to 3.7) increased risk of developing MCI at follow-up. The association was stronger for amnestic MCI (aMCI: HR 5.8; 95% CI 3.1 to 10.9) compared with global cognitive impairment (other cognitive impairment no dementia, oCIND: HR 2.2; 95% CI 1.5 to 3.3). ApoE-ε4 interacted with low mood in a synergistic fashion, increasing the risk of aMCI, while no interaction with psychiatric, vascular, frailty related or psychosocial factors was observed. Low mood at baseline, as opposed to low mood co-occurring with MCI, was associated with a 5.3-fold (95% CI 1.2 to 23.3) increased risk of progression to dementia in aMCI. In contrast, no association was found in oCIND. Conclusion: Low mood was more strongly associated with aMCI than with global cognitive impairment. Progression towards dementia was predicted only by low mood manifest in the prodromal stage of MCI. These findings indicate that low mood is particularly prominent in the very early stages of cognitive decline.